Impact of Pain on Activities of Daily Living in Older Adults: A Cross-Sectional Analysis of Korean Longitudinal Study of Aging (KLoSA) - Ambrish Singh; Sreelatha Akkala; Minakshi Nayak; Anirudh Kotlo; Naresh Poondla; Syed Raza; Jim Stankovich; Benny Antony (Geriatrics, 2024)
Pain, particularly musculoskeletal (MSK) and multi-site pain, significantly impacts activities of daily living (ADL) in the elderly, leading to a decline in overall quality of life (QoL). This study, comprising 7490 participants, (mean age: 69 ± 10; females: 57%) from the sixth wave of the Korean Longitudinal Study of Aging (KLoSA), aimed to assess the association between self-reported pain and ADL impairment among the elderly population. Notably, 62% of participants reported experiencing pain, with back pain being the most prevalent (36%) and stomachache the least (0.39%). A majority (61%) of individuals reported MSK-related pain. Additionally, 20% reported pain at one site and 0.03% experienced pain at 12 sites. ADL impairment was observed in 376 (5.0%) participants. Compared to those without pain, participants reporting moderate and severe pain had higher odds of ADL impairment [2.31 (95% CI, 1.66–3.21) and 2.98 (95% CI, 1.95–4.53), respectively]. Pain experienced in the shoulder, arm, wrist, back, hip, leg, and ankle had a significant association with ADL impairment, with ORs ranging from 2.66 (95% CI, 1.80–3.93; hip pain) to 1.36 (95% CI 1.07–1.72; back pain). Furthermore, multi-site pain was associated with higher ADL impairment [1–6 sites: OR: 1.49 (95% CI, 1.11–2.01); 7–12 sites: OR: 7.16 (95% CI, 3.60–14.26)]. These findings underscore the importance of addressing MSK and multi-site pain through targeted interventions, potentially enhancing ADL and contributing to an improved QoL among the elderly population.